Regeneration of caudal fin in Poecilia latipinna: Insights into the progressive tissue morphogenesis. (3rd April 2019) - Patel, Sonam; Ranadive, Isha; Desai, Isha; Balakrishnan, Suresh
ABSTRACT: Studies using fish fin as a model to understand the nuance of epimorphosis are gaining interest of lately. This study illustrates for the first time the daily changes in the tissue architecture of regenerating tail fin of Poecilia latipinna . Wound epithelium is formed within 24 hpa that eventually gets stratified into apical epithelial cap by 48 hpa. In the subsequent day, proliferating cells accumulate in front of each fin-ray marking the beginning of blastema. Distally these cells express signs of cartilage condensation by 4 dpa. However, ossification and subsequent transformation of actinotrichia to lepidotrichia was observed on 5 dpa. Subsequently, the regenerate grew at variable rate until it achieved the original size on 25 dpa. This result would serve as a worthwhile standard reference for further explorative studies that demand manipulation of a regulatory signal at a defined time point.